P768 Extended enoxaparin venous thromboembolism prophylaxis after surgery for inflammatory bowel disease: A cost-based decision-analysis. (16th January 2018) - Holubar, S; Dulai, P; Piazik, B; Finlayson, S; Udeh, B
Abstract: Background: Patients undergoing surgery for inflammatory bowel disease (IBD) are at an increased risk of venous thromboembolism (VTE) during their hospital stay and post-discharge. Optimal VTE prophylaxis, however, is not well defined in this population. In abdominopelvic surgery cancer patients, randomised trials showed extended enoxaparin (eENOX) prophylaxis was efficacious while decision-analytic study suggested extended heparin (eSQH) had greater economic efficiency but did not include patient adherence, and was prior to the availability of lower cost generic ENOX. This study used a cost-minimisation decision analysis to determine the optimal VTE prophylaxis strategy after surgery for IBD, addressing patient adherence and updated costs. Methods: A cost minimisation decision model was constructed comparing four strategies of VTE prophylaxis after surgery for IBD: (1) inpatient SQH 5000 units TID 10 days; (2) inpatient ENOX 40 mg daily 10 days; (3) eSQH 5000 units TID 30 total days (10 inpatient, 20 outpatient days) (eSQH); (4) eENOX 40 mg daily 30 total days (10 inpatient, 20 outpatient days). Model assumptions included: no prior history of VTE; only major bleeding required intervention; 90% of major bleeds were treated medically with transfusion of 2 units PRBC and 10% reoperation rate; and heparin-induced thrombocytopenia (HIT) occurred within 10 days of exposure. Rates of inpatient and outpatient VTE, adherence to outpatient treatment, and strategy specific complications including HIT and major bleeding for each strategy, and costs ($US) were abstracted from primary and secondary data sources. Deterministic and probabilistic sensitivity analysis were conducted to assess the robustness of the results to changes in model and parameter uncertainty. Results: At base case analysis, eENOX was the optimal strategy at $2.585/patient; eSQH was next strategy choice, incremental cost of $201 ($2768). Choice of optimal strategy was sensitive to VTE rates, HIT rates and drug costs. Sensitivity analysis demonstrated that eSQH was the optimal strategy when VTE rates with eENOX were >6.5% (vs. 5.7% in base case) and costs of eENOX were >$712 (vs. $528 in base case). eSQH became the optimal strategy when patient adherence rates were >85% (vs. 65% in the base case). Probabilistic sensitivity analysis determined the proportion of iterations that a strategy was the optimal choice. Conclusions: After surgery for IBD, extended ENOX was the optimal strategy (least cost). This is likely due to the availability of generic ENOX, reduced HIT risk, and increased adherence with eENOX resulting in greater VTE prevention relative to eSQH. The robustness of these results suggest a change in the standard of care for IBD VTE post-operative prophylaxis is indicated.